Elevated blood pressure in the paediatric population: the Nigerian experience - Animasahun, Adeola Barakat; Adewuyi, Adeniyi; Adejare Animasahun, Goodness; Ariyibi, Adedayo A.; Hughes-Darden, Cleo; Asinobi, Adanze (International Journal of Contemporary Pediatrics, 2026)
Background: The prevalence of hypertension in children is increasing, hence the need for updated information on the causes, clinical assessment, and treatment of childhood hypertension among Pediatricians. This study assessed the experiences and challenges in the management of childhood hypertension among Pediatricians in Nigeria. Methods: The study was a cross-sectional study conducted from responses from 73 Paediatric cardiologists and residents. An online self-administered structured questionnaire was used to collect information from participants. The results were analyzed using Statistical Package for the Social Sciences (SPSS) version 25. Results: Sixty-nine (94.5%) participants practiced at the tertiary level of health care. Respondents came from the country's geopolitical zones, mostly the south West (39.7%). About a third (31.5%) of children have elevated blood pressure on average. The availability of age-appropriate blood pressure monitoring instruments increased with age (from 60.3% in infants to 94.5% in adolescents). The nephrologist manages childhood hypertension in most centers (38.4). Secondary hypertension was the more common cause reported by respondents (91.8%), and acute glomerulonephritis (22.3%) and renal parenchymal disease (15.6%) were the leading causes. Almost half 34 (46.6%) are aware of guidelines for the management of hypertension in children, but only 64.7% of these use any. The calcium channel blockers (72.9%) are the leading antihypertensives used by respondents, and hydralazine is used for hypertensive emergencies. Conclusions: There are still challenges with the diagnosis and management of childhood hypertension in Nigeria. Providing age-appropriate BP measurement equipment and following management guidelines would enhance the care of childhood hypertension nationwide.